Conservative management of penetrating abdominal trauma (stab wound) - Loulah, Magdy Ahmed; Mostafa, Asem Fayed; El-Balky, Osama Soliman; El-Meligi, Abdel-Rahman Mohamed Mohamed Mohamed (International Surgery Journal, 2019)
Background: The aim of the study is to study the reliability of selective conservative management of the penetrating stab abdominal wounds. Trauma is one of the most important reasons of mortality. The mechanism that underlies the penetrating trauma relates to the mode of injury. The early diagnosis of hollow viscus injuries is difficult and a delay in the diagnosis of such injuries may be associated with increased morbidity and mortality. Focused assessment with sonography for trauma (FAST) is an effective for screening and initial classification of stable patients and confirmed by CT scan. The management of stable patients was either surgical exploration or selective non-operative interference with the optimal management of patients is yet to be fully elucidated for abdominal stab wounds (ASW). Methods: A prospective study of 40 patients with penetrating abdominal stab wounds between June 2017 and February 2018, at Damanhour Medical National Institute. Results: The mean age of our patients was 51.9±13.3 years with predominance of males and without predominance of any side to be affected and non-significant deviation from the normal values of hemodynamic signs. The presence of air under diaphragm in X-ray films signify abdominal penetration and ultrasonographic examination (FAST) document the diagnosis and help in following up of cases. Most of hemodynamically stable patients passed conservatively with a little rate of laparotomy. Conclusions: We concluded that there is still a role for conservative management in managing stable cases of penetrating stab abdominal wound.